Agronomic and reclamation strategies to enhance soil fertility, productivity and water accessibility - Rau, Alexey; Zhu, Kai; Nurlan, Balgabayev; Mirobit, Mirdadayev; Yessenkul, Kalybekova; Bek, Meymank Hozhaev; Nabiollina, Madina; Kurmanbek, Zhanymhan; Issakov, Yerlan; Antal, Sándor; Ujj, Apolka; Dávid, Lóránt Dénes (Frontiers in Sustainable Food Systems, 2023)
Introduction Over the last decade, yields and profitability of crops on agricultural lands in the Kyzylkum irrigation massif in the south of Kazakhstan, as well as soil fertility, have been decreasing. The Kyzylkum irrigation basin, located in the Syrdarya River basin, is affected by various factors such as agronomic practices, reclamation factors, and human activities including tourism. This study aims to monitor the yields of cotton and alfalfa in alfalfa-cotton crop rotations in the Kyzylkum irrigation massif, assess soil fertility after alfalfa and cotton cultivation under production conditions, and evaluate the profitability of water consumption. Methods The research methodology involved experimental and observational studies conducted on a nine-pole alfalfa-cotton crop rotation area in the Kyzylkum basin within the Syrdarya river basin. The study was conducted on three farms: Didar, Toishy, and Ali-Myrza. Productivity, soil fertility after crop cultivation, and profitability of water consumption were determined through these studies. Results The study found that the Ali-Myrza farm experienced a 21% increase in cotton yield, a 24% increase in alfalfa yield, a 36% increase in profit from crop rotation, a 34% increase in profitability, and a 5-6% increase in water consumption. After alfalfa rotation, the Ali-Myrza farm recorded the highest cotton yield at 3.5 t/ha and a profit of 1,316 euros/ha. However, in the following year, cotton yields decreased to 2.52 t/ha, and profits dropped to 576 euro/ha. The first year of alfalfa cultivation resulted in a yield of 10 t/ha and a profit of 462 euro/ha, which increased to 14 t/ha and 967 euro/ha in the subsequent year. Soil analysis revealed that after two years of growing alfalfa in a six-pole rotation, the root mass in the top 20 cm of soil reached 8.89 t/ha. In contrast, rotations with seven (Toishy) and nine (Didar) crops resulted in lower root masses of 4.68 t/ha and 3.47 t/ha, respectively. The corresponding humus content was 1.65%, 1.40%, and 1.1%, respectively. Discussion Comparing the seven and nine-pole rotations of alfalfa and cotton, the six-pole rotation demonstrated significant improvements in soil fertility (30-40% increase), cotton yield (18-23% increase), alfalfa yield (20-28% increase), and water consumption (5-6% increase). These findings confirm the effectiveness of the alfalfa-cotton rotation method in enhancing soil fertility, productivity, water efficiency, and grey soil productivity in Kyzylkum irrigated fields. The results obtained from this study can be applied in cotton farms in South Kazakhstan that use nine-layer cotton and alfalfa rotations. Furthermore, the findings have implications for cotton cultivation in any country worldwide.